Endoscopic Treatment of Iatrogenic Perforation of Sigmoid Diverticulum: A Case Report of Multidisciplinary Management - Giacomo Emanuele Maria Rizzo; Giuseppina Ferro; Giovanna Rizzo; Giovanni Di Carlo; Alessandro Cantone; Gaetano Giuseppe Di Vita; Carmelo Sciumè (Clinical Endoscopy, 2022)
Iatrogenic perforations are severe complications of gastrointestinal endoscopy; therefore, their management should be adequately planned. A 77-year-old man with a history of diverticulosis underwent a colonoscopy for anemia. During the procedure, an iatrogenic perforation occurred suddenly in the sigmoid colon, near a severe angle among the numerous diverticula. Through-the-scope clips were immediately applied to treat it and close mucosal edges. Laboratory tests showed increased levels of inflammation and infection, and although there were no complaints of abdominal pain, the patient had an extremely distended abdomen. A multidisciplinary board began management based on a conservative approach. Pneumoperitoneum was treated with computed tomography-assisted drainage. After 72 hours, his intestinal canalization and laboratory tests were normal. Though this adverse event is rare, a multidisciplinary board should be promptly gathered upon occurrence, even if the patient appears clinically stable, to consider a conservative approach and avoid surgical treatment.